HUBUNGAN SIMTOM KECEMASAN DAN SIMTOM DEPRESI TERHADAP NILAI BLOK PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA ANGKATAN 2019 - MUHAMMAD IKHSAN FAJAR PRASETYO; ANDRI YUNAFRI (JURNAL ILMIAH SIMANTEK, 2021)
Based on the 2013 Basic Health Research (Riskesdas) the prevalence of the Indonesian population experienced nationalmental emotional disorders such as anxiety disorders by 6%. Depression and anxiety can affect student learning outcomes,because depression and anxiety tend to produce perceptual distortions and confusion. This distortion and confusion willdisrupt students' learning by weakening their ability to focus, decreasing memory, and interfering with the ability to relate onething to another. Symptoms of depression and anxiety that appear in individuals are decreased concentration, sleepdisturbances and loss of enthusiasm for daily activities. All three are part of internal factors that affect learning achievement,so that depression can have an impact on academic achievement. To find out the relationship between the level of anxietysymptoms on the academic achievement index in the students class 2016 in the Faculty of Medicine, University ofMuhammadiyah Sumatera Utara. This study was descriptive analytic with a cross sectional design. The results of this studyused the Kruskal-Wallis test. Kruskal-Wallis test analysis obtained the value of P Value as indicated by the value of Asymp.Sig is 0.005 which means there is no influence on the level of anxiety symptoms on the academic achievement index.There is no correlation between the level of anxiety symptoms towards the academic achievement index in the students class2016 in the Faculty of Medicine, University of Muhammadiyah Sumatera Utara.